Investigation of TNBC in vitro Antiproliferative Effects of Versatile Pirrolo[1,2-a]quinoxaline Compounds - Perri, Mariarita; Aiello, Francesca; Cione, Erika; Carullo, Gabriele; Amendola, Luisa; Mazzotta, Sarah; Caroleo, Maria Cristina (Frontiers in Molecular Biosciences, 2019)
The triple-negative breast cancer (TNBC) is characterized by a more aggressive nature and poorer prognosis, nowadays none pharmaceutical approach is still available. For this reason, the research of new active compounds and attractive targets represents an interesting field. In this context MDA- MB-231 cell line was selected to evaluate the anti-proliferative effects of new [1,2-a]-pyrroloquinoxaline derivatives. The MTT assay revealed that the amine forms of synthesized molecules were more active compared to iminic ones at 72h of incubation. The anti-proliferative effect of the most promising compounds highlighted the formation of autophagic vacuoles.